Closing small open economy models - Stephanie Schmitt-Grohe; Martín Uribe (Rutgers University, Department of Economics, 2001)
The small open economy model with incomplete asset markets features a steady state that depends on initial conditions. In addition, equilibrium dynamics posses a random walk component. A number of modifications to the standard model have been proposed to induce stationarity. This paper presents a quantitative comparison of these alternative approaches. Five different specifications are considered: (1) A model with an endogenous discount factor (Uzawa-type preferences); (2) A model with a debt-elastic interest-rate premium; (3) A model with convex portfolio adjustment costs; (4) A model with complete asset markets; (5) A model without stationarity-inducing features. The main finding of the paper is that all models deliver virtually identical dynamics at business-cycle frequencies, as measured by unconditional second moments and impulse response functions. The only noticeable difference among the alternative specifications is that the complete-asset-market model induces smoother consumption dynamics.
Keywords: F41; 330; Complete and Incomplete Asset Markets; Small Open Economy; Stationarity; Kleines-offenes-Land; Finanzmarkt; Unvollkommener Markt; Anpassungskosten; Theorie